Effect of Methods of Drying on Viability, Storability and Seedling Performance of Neem (Azadirachta indica A. Juss.) Seeds - Kumar, Devendra; Mishra, Dhruv Kumar; Singh, Balbir; Singh, Ved Pal (Indian Forester, 2008)
Neem seeds are short lived and require quicker and more uniform drying to maintain viability and vigour. After proper cleaning, seeds were dried in the sun, shade, dryer at 45±1°C and 55±1°C. Seeds dried in shade, reached at 7.2% EMC (equilibrium moisture content) after 168 hours. while seeds dried in dryer at 55±1°C reached at 5% EMC within 40 hours followed by Sun drying (56 hours) and dryer at 45±1°C (144 hours). After reaching EMC, seeds were tested for their viability and vigour under controlled conditions and in nursery too. Seeds were sown in nursery upto 60 days for evaluating the seedling performance in terms of total seedling length, number of leaves, collar diameter, total biomass and vigour index. All seed lots were stored in open containers at ambient room temperature (35±5°C) and tested at various intervals of storage viz. Fresh/0, 60, 90, 105, 120, 158, 180 and 275 days. Shade dried seeds showed higher mean viability period (P50) of 172 days followed by seed dried through drier at 45±1°C (113 days) as compared to sun-dried seeds (40 days). Seeds dried in shade found best followed by dryer at 45±1°C in terms of seed and seedling performance and storability.